Improvement of performances of complex non-platinum electrode materials for hydrogen evolution - P. Paunovic, O. Popovski, A. Dimitrov, D. Slavkov, E. Lefterova, S. Hadzi Jordanov (Elsevier, 2006)
Structural and electrochemical characteristics of hypo–hyper d-electrocatalytic materials aimed for preparation of electrodes for hydrogen evolution were studied and modified in order to improve their performances. All studied materials were of general composition 10% Ni + 18% TiO2 +C. All materials were prepared of amorphous or crystalline TiO2, crystalline Ni or NiCo (10–20 nm) and Vulcan XC-72, by sol–gel procedure. Both, material’s intrinsic catalytic activity and surface area were affected by applied modifications. As a result, the electrocatalytic activity was improved, e.g. transformation of TiO2 into anatase form lowers the HER overpotential for 60mV. Introduction of MWCNTs was even more effective, lowering η for 120mV. Co addition to metallic phase lowers η for utmost 195mV. Combined modification of TiO2 and carbon substrate lowers η for 145mV, while the complete modification of all three catalyst’s components was the most effective with 230mV decrease of overpotential.